2019
DOI: 10.3389/fneur.2019.01200
|View full text |Cite
|
Sign up to set email alerts
|

Combined Optokinetic Treatment and Vestibular Rehabilitation to Reduce Visually Induced Dizziness in a Professional Ice Hockey Player After Concussion: A Clinical Case

Abstract: Background: The appropriate detection and therapy of concussion symptoms are of great importance to avoid long-term impairment and absence from pre-concussive activities, such as sport, school or work. Post-traumatic headache and dizziness are known as risk factors of persistent symptoms after a concussion. Dizziness has even been classified as a predictor for symptom persistence. One type of dizziness, which has never been considered is visually induced dizziness (VID) often develops as a consequence of vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…A relationship between PPPD and migraine has been suggested [ 97 ]. Interestingly, PPPD can be visually triggered [ 98 ], as can motion sickness. Most likely motion sickness and PPPD intermingle.…”
Section: Interictal Visual Symptomsmentioning
confidence: 99%
“…A relationship between PPPD and migraine has been suggested [ 97 ]. Interestingly, PPPD can be visually triggered [ 98 ], as can motion sickness. Most likely motion sickness and PPPD intermingle.…”
Section: Interictal Visual Symptomsmentioning
confidence: 99%
“…Case studies have shown VOR disruption in those with PCS (25,26). Common complaints of vestibular dysfunction include dizziness, vertigo, nausea, fogginess, unsteady gait, and postural instability (20,27). Symptoms associated with oculomotor dysfunction include double vision, di culty tracking objects or focussing, motion sensitivity, photophobia, eye strain, and headache (20,27).…”
Section: Introductionmentioning
confidence: 99%
“…Common complaints of vestibular dysfunction include dizziness, vertigo, nausea, fogginess, unsteady gait, and postural instability (20,27). Symptoms associated with oculomotor dysfunction include double vision, di culty tracking objects or focussing, motion sensitivity, photophobia, eye strain, and headache (20,27). Importantly, evidence has shown that these symptoms of vestibulo-ocular dysfunction are strong predictors of delayed recovery in PCS (19,20,23).…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence, or worsening, of dizziness during exposure to environments with complex visual stimuli (e.g. supermarket aisles, busy crossroads) is commonly reported by concussed patients [ 12 , 13 ]. Such symptoms are well known in patients with vertigo of various aetiologies and have been defined as a syndrome of visual vertigo [ 14 ] or visually induced dizziness (VID) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the reports on concussed patients who present symptoms compatible with visual dependence [ 12 , 13 ], we hypothesized that in selected concussed patients with persisting, strong dizziness after visual stimuli the VSM is overacting when it extracts self-motion information from visual cues. To evaluate this hypothesis, we analysed OKAN of patients who showed signs and symptoms supporting impaired central integration of visual information after a concussion.…”
Section: Introductionmentioning
confidence: 99%